Retracted: Daidzin inhibits RANKL‐induced osteoclastogenesis in vitro and prevents LPS‐induced bone loss in vivo. Issue 4 (30th October 2018) - Wei, Gejin; Liang, Tihong; Wei, Chengming; Nong, Xiaolian; Lu, Qiteng; Zhao, Jinmin
Abstract: Osteoclasts are multinuclear giant cells responsible for bone resorption in bone loss diseases, including rheumatoid arthritis, periodontitis, and the aseptic loosening of orthopedic implants. Because of injurious side effects with currently available drugs, it is necessary to continue research novel bone‐protective therapies. Daidzin, a naturally occurring isoflavone found in leguminous plants, has numerous beneficial pharmacologic effects, including anti‐cancer, anti‐cholesterol, and anti‐angiocardiopathy, promoting osteoblasts differentiation, and even anti‐osteoporosis. However, the effect of daidzin on the regulation of osteoclast activity has not yet been investigated. In this study, our study showed that daidzin significantly inhibited receptor activator of nuclear factor‐kB ligand (RANKL)‐induced osteoclast differentiation of bone marrow macrophages and the hydroxyapatite‐resorbing activity of mature osteoclasts by inhibiting RANKL‐induced NF‐kB signaling pathway. In addition, daidzin could inhibit the expression of osteoclast marker genes, including nuclear factor of activated T cells cytoplasmic 1 (NFATc1), cellular oncogene fos (c‐Fos), tartrate‐resistant acid phosphatase (TRAP), and cathepsin K (CTSK). Consistent with in vitro results, daidzin inhibited lipopolysaccharide‐induced bone loss by suppressing the osteoclast differentiation. Together our data demonstrated that daidzin inhibits RANKL‐induced osteoclastogenesis through suppressing NF‐ĸB signaling pathway and that daidzin is a promising agent in the treatment of osteolytic diseases. Abstract : 1. Daidzin inhibits osteoclastogenesis and stimulats osteoblast formation. 2. Daidzin reduces ovariectomy‐induced bone loss.